The Position of Marginalized Groups in the Elite Captured Local Level Planning Process in Nepal - Acharya, Keshav K.; Dhungana, Raj Kumar; Guragain, Hari Prasad (Nepal Public Policy Review, 2022)
The participatory planning and budgeting process at the local level encourages citizens to participate in the selection, implementation, and management of development plans. Over the last few decades, the elite captured planning process in Nepal is criticized for being unfair to the marginalised groups. This paper, through a critical qualitative assessment of the local level planning process, explored the role of political actors and the marginalised communities in the local level decisions. It adapted the Weberian idea of power networks where elites can implement their will, even against the will of others. It revealed that the influence of traditional political elites - i.e., Panchas – has shifted to the newly elected or selected political elites, the neo-elites, represented by the local leaders including elected Mayors, with some exceptions. The neo-elite control in the local planning process is as strong as it was in the past despite there being progressive provisions in the constitution, laws and systems. The distribution of plans among influential leaders, bhagbanda, is widely practised at the local level. As a result of these progressive provisions and the follow-up of the seven-step planning process, the neo-elites started consulting with the representatives of the marginalised communities in planning-related decisions. It is recommended that the political parties re-orient the neo-elites to be pro-people. Neo-elites who are inclusive, and follow the progressive laws and the formal systems of the nation, are to be prioritized.